A DESCRIPTIVE ANALYSIS OF NOUN PHRASES IN EFL STUDENTS’ ESSAYS - Maida Norahmi; Olga Dona Retsi; Susan Ira Nova; Lesly Martha Cecylia Meka; Tutik Haryani; Sovia Rahmaniah; Cendikia Flory Aristia; Siti Munawarah; Windi Fitriyani (STKIP Persada Khatulistiwa Sintang, 2026)
This study explores the structure and function of noun phrases (NPs) in English essays written by undergraduate EFL students at Universitas Palangka Raya. Employing a qualitative descriptive method, it analyzed 78 essays to identify and classify types and frequencies of noun phrase modifiers based on Biber et al.’s (2021) syntactic framework. The findings revealed that students predominantly used premodified noun phrases (85%), with determiners and adjectives as the most frequent modifiers, while postmodified noun phrases (15%) were less common and mostly realized through prepositional phrases. More complex postmodifiers, such as adjectives, participle clauses, infinitive clauses, adverbs, and appositives appeared infrequently, indicating limited syntactic variety. The dominance of simpler noun phrase structures suggests that students demonstrate intermediate syntactic competence, emphasizing clarity and economy in expression. These tendencies are attributed to pedagogical focus on basic grammar and first-language influence, particularly from Bahasa Indonesia. The study recommends enhancing grammar instruction by integrating activities that promote the use of complex noun phrase constructions in academic writing.